Fluid Intake History and Counseling in Pediatric Outpatients. (February 2014) - Nelson, Courtney E.; Marquez, Maria; Rappaport, David I.; Sharif, Iman
Objective . To determine if ( a ) during well visits physicians are discussing 6 common fluids and ( b ) if there is any association between fluid discussion and patient age, gender, or body mass index. Methods . We performed a retrospective chart review of 500 pediatric well visits. We analyzed the relationships between history and/or counseling on fluid intake and patient age, gender, and body mass index percentile using logistic regression and likelihood ratio chi-square testing. Results . Caffeinated beverages were discussed more with overweight/obese patients compared with normal weight patients. Juice, caffeinated, and carbonated beverages were all discussed more with obese patients compared with overweight patients. Water, carbonated, and caffeinated beverages were discussed more with older patients, and milk with younger patients. Juice was discussed more with female patients. Conclusion . Pediatricians discuss high-calorie fluids more frequently with obese children but not more frequently with overweight children, which may be an optimal time to prevent obesity.